Telaah Hermeneutika atas Poligami - Sanurdi, Sanurdi (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
Islamic ideology is the interpretation of Moslems to the Holy Qur’an. One of the interpretation potentially causes some endless controversy. Polygamy discourse arouse because of the different frame and it implies to the different understanding. Hermeunetic frame as an alternative solution, emphasize to the language grammatical and historical dialect about the polygamy law understanding.